Analytical solution for temperature field of nonmetal cooling pipe embedded in mass concrete. (25th July 2019) - Chen, Guorong; Ding, Xiaofei; Cai, Mingxuan; Qiao, Wenzheng
Highlights: A non-dimensional differential equation is presented for cooling water pipe. Error analysis of the first and first two terms of infinite series is carried out. An exponential function is used to fit the combination of Bessel functions. A concise solution of partial differential equation is given. Abstract: Non-metal cooling water pipe is widely used in temperature control of mass concrete structures. However, the previous calculation method for water pipe cooling contained a Bessel function, which makes the calculation very cumbersome. In this paper, the theoretical solution and simplification of cooling of non-metal pipes, compared with the cooling of metal pipes, are studied. It is found that the form of the theoretical solution obtained by the separation variable method can be simplified to an exponential function form. A new formula is presented herein for the theoretical solution of the temperature field in pipe cooling. For non-dimensional parameters, the numerical values of these parameters for the formula are given, which are convenient for direct calculation.